2022
DOI: 10.1039/d2nr04161h
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial layering of hydrocarbons on pristine graphite surfaces immersed in water

Abstract: Atomic-scale imaging of liquid water on graphitic surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…3D AFM images showed that the interfacial water structure was characterized by interlayer distances in the 0.3 nm range. That value was in agreement with the distance between the first and the second peak of the water density profile predicted by MD simulations on graphene or graphite surfaces. ,, Additional 3D AFM experiments involving larger volumes of water also showed interlayer distances consistent with the presence of hydration layers . Furthermore, it coincided with the values reported by an early X-ray reflectivity measurement .…”
Section: Complexity Of Liquid Water Interfaces On Graphite and 2d Mat...supporting
confidence: 88%
See 4 more Smart Citations
“…3D AFM images showed that the interfacial water structure was characterized by interlayer distances in the 0.3 nm range. That value was in agreement with the distance between the first and the second peak of the water density profile predicted by MD simulations on graphene or graphite surfaces. ,, Additional 3D AFM experiments involving larger volumes of water also showed interlayer distances consistent with the presence of hydration layers . Furthermore, it coincided with the values reported by an early X-ray reflectivity measurement .…”
Section: Complexity Of Liquid Water Interfaces On Graphite and 2d Mat...supporting
confidence: 88%
“…A large number of 3D AFM images were obtained on graphite, graphene, and few-layer TMDCs surfaces immersed in water. Those images showed an interfacial water structure characterized by the presence up to three solvation layers parallel to the graphite surface. ,,, The separation between the layers was 0.5 nm (average value). This value was about 0.2 nm larger than the one expected for hydration layers (0.3 nm).…”
Section: Complexity Of Liquid Water Interfaces On Graphite and 2d Mat...mentioning
confidence: 99%
See 3 more Smart Citations